Gut Microbiota Modulation: A Novel Strategy for Rheumatoid Arthritis Therapy - Vitaly Chasov; Elvina Gilyazova; Irina Ganeeva; Ekaterina Zmievskaya; Damir Davletshin; Aygul Valiullina; Emil Bulatov (Biomolecules)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that leads to joint inflammation, progressive tissue damage and significant disability, severely impacting patients’ quality of life. While the exact mechanisms underlying RA remain elusive, growing evidence suggests a strong link between intestinal microbiota dysbiosis and the disease’s development and progression. Differences in microbial composition between healthy individuals and RA patients point to the role of gut microbiota in modulating immune responses and promoting inflammation. Therapies targeting microbiota restoration have demonstrated promise in improving treatment efficacy, enhancing patient outcomes and slowing disease progression. However, the complex interplay between gut microbiota and autoimmune pathways in RA requires further investigation to establish causative relationships and mechanisms. Here, we review the current understanding of the gut microbiota’s role in RA pathogenesis and its potential as a therapeutic target.